Technology-Supported Aestheticized Educational Environments: Effects on Designers’ and Artists’ Aesthetic Consciousness - Olha Kostiuk; Nataliia Dihtiar; Inna Hurzhii; Oleksii Sobolevskyi; Oleksandr Shpetnyі (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigated the effects of integrating digital visual learning resources within an aestheticized educational environment on the development of aesthetic consciousness among undergraduate design and art students. The study also examined changes in cognitive, value-semantic, and activity-related dimensions of aesthetic development. Methodology: A quasi-experimental design was employed involving 63 undergraduate students enrolled in art and design programs. Data were collected using questionnaires, essays, and practical creative tasks. The intervention combined Ukrainian decorative art, project-based workshops, exhibition activities, reflective learning tasks, and technology-supported visual learning materials. Data were analyzed using Fisher’s angular transformation (φ*), Cohen’s h effect size, independent-samples t-tests, and exploratory ANCOVA. Main Findings: Students in the experimental group demonstrated significantly higher post-test outcomes than those in the control group across all assessed dimensions. High-level achievement increased in knowledge of Ukrainian culture (59.37%), knowledge of traditional wall painting (62.50%), value-semantic development (60.20%), and activity-related performance (40.60%). Exploratory ANCOVA confirmed significant group effects across all criteria (p < 0.001). The findings indicate that integrating digital visual learning resources into an aestheticized educational environment was associated with enhanced aesthetic consciousness and creative engagement. Novelty/Originality of this study: This study proposes and empirically validates a culturally grounded educational model integrating aestheticized learning environments, Ukrainian decorative art, reflective practice, project-based learning, exhibition activities, and technology-supported visual resources. Unlike research focusing exclusively on digital technologies or aesthetic education, the study demonstrates that combining cultural heritage, creative practice, and structured learning experiences effectively enhances students’ aesthetic consciousness and creative engagement.